Quorum Sensing Controls Exopolysaccharide Production in Sinorhizobium meliloti - Marketon, Melanie M. (American Society for Microbiology, 2003)
Sinorhizobium meliloti is a soil bacterium capable of invading and establishing a symbiotic relationship with alfalfa plants. This invasion process requires the synthesis, by S. meliloti, of at least one of the two symbiotically important exopolysaccharides, succinoglycan and EPS II. We have previously shown that the sinRI locus of S. meliloti encodes a quorum-sensing system that plays a role in the symbiotic process. Here we show that the sinRI locus exerts one level of control through regulation of EPS II synthesis. Disruption of the autoinducer synthase gene, sinI, abolished EPS II production as well as the expression of several genes in the exp operon that are responsible for EPS II synthesis. This phenotype was complemented by the addition of acyl homoserine lactone (AHL) extracts from the wild-type strain but not from a sinI mutant, indicating that the sinRI-specified AHLs are required for exp gene expression. This was further confirmed by the observation that synthetic palmitoleyl homoserine lactone (C(16:1)-HL), one of the previously identified sinRI-specified AHLs, specifically restored exp gene expression. Most importantly, the absence of symbiotically active EPS II in a sinI mutant was confirmed in plant nodulation assays, emphasizing the role of quorum sensing in symbiosis.